A digital tool for life cycle assessment in construction projects - Irene Campo Gay; Lars Hvam; Anders Haug; George Q. Huang; Robert Larsson (Developments in the Built Environment)
The building and construction industry is responsible for around 40% of global greenhouse gas emissions, driving the urgent need for new regulations. As such, the life cycle assessment (LCA) methodology has become fundamental for evaluating environmental impacts. Despite the need for digital tools to support environmental performance evaluations, the lack of guidance on developing such tools hinders their implementation. This article presents an automated configuration approach to develop digital tools in construction, which facilitates the proactive comparison of design choices and reduces CO2 emissions. We demonstrate its application by implementing it at Heidelberg Materials Cement Sverige in Sweden. The results reveal that the LCA digital tool influences decision-making and efficiently quantifies global warming potential in the early project stages and reduces product-related CO2 emissions by up to 40%. Furthermore, the findings highlight greater accuracy in LCA calculations compared to current manual methods and quicker design iterations thanks to real-time information.